Comorbid Traumatic Brain Injury and Visual Impairment: Vocational Rehabilitation Service Provision and Agency-Level Outcomes. (January 2020) - McDonnall, Michele C.; Cmar, Jennifer L.; Lund, Emily M.
Introduction: The purpose of this study was to investigate how services are provided to state–federal vocational rehabilitation consumers with comorbid traumatic brain injury (TBI) and visual impairment and the prevalence of and competitive employment rates for this population. Methods: We utilized a mixed-methods approach by incorporating interview data from 51 vocational rehabilitation agency administrators (to identify strategies used to serve these consumers) and case service data (to identify prevalence and competitive employment rates at the agency level). We combined the data to examine the relationship between strategies used and the prevalence of and employment outcomes for this population. A modified grounded theory approach was used for qualitative data analysis and descriptive statistics, and analyses of variance were used for quantitative data analyses. Results: Strategies used to serve these consumers included collaboration between counselors, involvement of external organizations, specialized TBI units or caseloads, staff training in TBI, and personnel with dual expertise in TBI and visual impairment. Over a third of agency administrators reported that they did not do anything special or different to serve this population. The average percentage of consumers with visual impairments who also had TBIs being served by agencies was 2.1%. Their average competitive employment rate by agency was 43.2%. Employing staff with dual expertise in TBI and visual impairment was associated with serving a greater percentage of consumers and having a higher competitive employment rate. Discussion: No agencies had a unique service delivery program or method to serve this population, perhaps due to its low prevalence. Agencies had substantial variability in the proportion of consumers with TBI and visual impairment served and their competitive employment rates.Implications for practitioners: Training vocational rehabilitation professionals to develop expertise in both TBIs and visual impairments may help agencies better serve these consumers.